Case Report: Management Approach and Use of Extracorporeal Membrane Oxygenation for Diffuse Alveolar Hemorrhage After Pediatric Hematopoietic Cell Transplant - Fan, Kimberly; Hurley, Caitlin; McNeil, Michael J.; Agulnik, Asya; Federico, Sara; Qudeimat, Amr; Saini, Arun; McArthur, Jennifer; Morrison, Ronald Ray; Sandhu, Hitesh; Shah, Samir; Ghafoor, Saad (Frontiers in Pediatrics, 2021)
Introduction: Diffuse alveolar hemorrhage (DAH) is an early pulmonary complication of hematopoietic cell transplantation (HCT) associated with severe hypoxemic respiratory failure and mortality. Extracorporeal membrane oxygenation (ECMO) support is often used for respiratory failure refractory to conventional interventions; however, its use has been limited in HCT patients with DAH due to potential for worsening alveolar hemorrhage and reported high mortality. Case Presentation: We report two cases of DAH following HCT who developed refractory hypoxemic respiratory failure despite cessation of bleeding and were successfully supported with ECMO. Conclusion: DAH after HCT should not automatically preclude ECMO support; rather, these patients must be evaluated individually for ECMO within the context of their overall clinical picture